Unexpected fragmentation of bis(triarylstannanethiocarbonyl)disulfides, formation and X-ray structure of triarylstannyl triarylstannanecarbodithioates - Kulai, Ihor; Brusylovets, Oleksii; Saffon, Nathalie; Voitenko, Zoia; Mazières, Stéphane; Destarac, Mathias (Київський національний університет імені Тараса Шевченка, 2015)
The synthesis of bis(triarylstannanethiocarbonyl)disulfides was attempted by oxidation of lithium triaryl stannane carbodithioates with molecular iodine. Unexpectedly,the desired compounds are highly unstable and undergo subsequent fragmentation giving triarylstannyl triarylstannanecarbodithioates. The proposed mechanism for this transformation assumes intramolecular nucleophilic substitution with formation of six-membered ring transition complex, stabilized by interaction between tin and thiocarbonyl sulfur atom. Obtained compounds were identified by mass-spectrometry and NMR spectroscopies, and their structures were analyzed by X-ray diffraction. These molecules show the existence of intramolecular non-bonding interactions between the sulfur atoms of the thiocarbonyl moieties and tin atoms. These interactions reflect the tin - sulfur affinity and are the main driving force in the fragmen tation of bis(triphenylstannanethiocarbonyl)disulfides. Supplementary information (CIF_file_1, CIF_file_2)
Keywords: stannanecarbodithioate; intramolecular nucleophilic substitution; X-ray analysis; intramolecular interaction